Staying cool in the compact city: Vacant land and urban heating in Philadelphia, Pennsylvania. (February 2017) - Pearsall, Hamil
Abstract: This study analyzes socio-spatial patterns in land surface temperature (LST) and vacant land across Philadelphia, Pennsylvania, a city with an estimated 30, 000–40, 000 vacant lots and a history of increased mortality associated with extreme heat events. Urban sustainability planning efforts typically encourage a compact city to improve quality of life and reduce sprawl, yet these same characteristics contribute to surface heating and the urban heat island effect (UHI). City officials often aim to redevelop vacant lots into conventional, tax-generating uses (e.g. commercial, industrial, or residential development), but few studies consider the role of vacant land in urban heating. This study employs LST and normalized difference vegetation index (NDVI) metrics derived from Landsat 8 imagery acquired on August 7, 2014, data on imperviousness from the 2011 National Land Cover Dataset (NLCD), vacant parcels from the City of Philadelphia, and socioeconomic data on median household income and minority populations from the American Community Survey (ACS) 2009–2013 5-year estimates at the Census Block Group level. The results of this study indicate that neighborhoods with low socio-economic status are hotter and have more vacant lots than their wealthier counterparts. This study points towards the potential of green conversions of vacant lots for mitigating inequities in urban heating in the most socially and economically vulnerable neighborhoods across the city. Highlights: Study analyzes socio-spatial patterns in heat exposure and vacant land. Temperature hot spots have higher poverty rates and more vacant lots. Green conversions of vacant lots could mitigate heating in hot spots.